2011
DOI: 10.1152/ajpheart.00120.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oral exposure to the aldehyde pollutant acrolein induces dilated cardiomyopathy

Abstract: Environmental triggers of dilated cardiomyopathy are poorly understood. Acute exposure to acrolein, a ubiquitous aldehyde pollutant, impairs cardiac function and cardioprotective responses in mice. Here, we tested the hypothesis that chronic oral exposure to acrolein induces inflammation and cardiomyopathy. C57BL/6 mice were gavage-fed acrolein (1 mg/kg) or water (vehicle) daily for 48 days. The dose was chosen based on estimates of human daily unsaturated aldehyde consumption. Compared with vehicle-fed mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 46 publications
4
80
0
1
Order By: Relevance
“…50 Interestingly, acrolein is both an initiator and an end-product of lipid peroxidation. It has been suggested that acrolein causes the alteration of target molecules via oxidative stress, generation of excess reactive oxygen species, and alteration of endogenous antioxidants, such as depletion in GSH level in target cells.…”
Section: Discussionmentioning
confidence: 99%
“…50 Interestingly, acrolein is both an initiator and an end-product of lipid peroxidation. It has been suggested that acrolein causes the alteration of target molecules via oxidative stress, generation of excess reactive oxygen species, and alteration of endogenous antioxidants, such as depletion in GSH level in target cells.…”
Section: Discussionmentioning
confidence: 99%
“…The heating of glycerol can form acrolein, which is an irritant and oxidizing agent thought to contribute to adverse pulmonary and cardiovascular effects of cigarette smoking. [83][84][85] Analyses of emissions from cigarettes have found primarily formaldehyde, acetaldehyde, and acrolein, along with low levels of toluene, xylene, benzene, and butadiene. 86 Although these compounds are potentially toxic, the levels in e-cigarette emissions are many-fold lower than those found in cigarette smoke and in some cases similar to those found in the mist of medicinal nicotine inhalers.…”
Section: Carbonyls and Other Volatile Chemicalsmentioning
confidence: 99%
“…The study found 2,879 differentially expressed genes of the 45,037 transcripts in the microarray, highlighting the potential influence of synthetic musk on embryonic development. Another study (34) showed that chronic oral exposure to acrolein, an aldehyde pollutant, caused dilated cardiomyopathy in mice. The effects of human exposure to acrolein should be studied further to investigate possible connections between chronic exposure, cardiomyopathy, and heart failure.…”
Section: Animal Modelsmentioning
confidence: 99%